Drug Legalization and Decriminalization Beliefs Among Individuals with and without a History of Substance Use - Park, Brandon (Journal of drug issues, 2025)
Drug legalization and decriminalization policy has changed in recent years. This study examined attitudes regarding drug legalization and decriminalization among persons who use substances, a perspective that can provide a unique view on legalization/decriminalization. A nationwide sample of 515 adults with and without substance use were surveyed online to assess opinions on drug legalization and decriminalization. Legalization/decriminalization beliefs were rated on an 11-point scale (0, “strongly disagree”; 10, “strongly agree”) and compared across demographic and drug use characteristics. Among persons with lived experiences in substance use, direct use of certain substances such as opioids or stimulants appears to be associated with low levels of support for legalization and modest support for decriminalization. Individuals with cannabis use largely supported cannabis legalization and decriminalization. Reasons behind ratings by persons with opioid and cocaine use should be further evaluated. Evolving social acceptance of illicit drug use may shift attitudes over time.